EXPERIMENTAL STUDY OF ELEMENTARY MATHEMATICAL CONCEPTS OF STUDENTS WITH INTELLECTUAL DISABILITIES - Hamidova Muyassar (The Bioscan, 2025)
This article reveals the state of development of elementary mathematical skills in mentally retarded students. In mentally retarded students, their perception of size, their solution of simple issues, their quantitative perception, their understanding of geometric shape, the state of spatial and temporal representations were identified and analyzed. As a result of an experimental study, students were examined by mentally retarded children about their perception of size, solving simple issues, quantitative perceptions, concepts about geometric shape, the state of appropriation of spatial and temporal representations. Keywords Images of size, simple issues, quantitative representations, geometric shape, spatial and temporal representations, placement by size, example, counting, adaptation.